The Vice of the Academic Emptyness - Sauka, Donatas (Sociologija. Mintis ir veiksmas, 1999)
The article discusses the cultural situation in Lithuania: the monologic nature of intellectual discourse, lack of alternative thought traditions. Apart from the episodic cases of international recognition, the field of art is dominated by commercial journalism, aesthetic freedom is perceived as legalization of destruction. The art is left with the function of provocation and irritation, but excludes the questions of meaning. The social science plays a secondary role in the consumer society. In the search for the alternatives to fill the intellectual emptiness, the ideas of Emile Durkheim could be considered. The notion of an intellectual as a critic whose task is to think of the collective aims is of special importance. Its justification comes not from scientific argument. It is rather an essayistic attempt to provide an image that is not bound by the pragmatic political and economic interests.